Livelihood Analysis of Multicrop Farmer Households in Manyaran District, Wonogiri Regency - Ridha Ulilalbab Azizah; Nur Auliatun Nissa Zulfa; Nurmalasari Nevia; Restutami H Indah; Hidayah Nurul (SHS Web of Conferences)
This study examines the horticultural diversification strategies of rice farmers in Manyaran Village, Wonogiri Regency, to enhance income and sustainability amidst the challenges of high capital and production costs, low yields, and market prices in rice farming. The research aims to contribute to broader development goals, including poverty reduction and food security, by investigating how diversification can improve economic outcomes for farmers. A mixed-method approach combining quantitative surveys and qualitative interviews was used to collect data on production costs, yields, and income from both rice and horticultural crops. Socioeconomic factors influencing diversification decisions were also explored. The results reveal that diversifying into horticulture has helped reduce production costs and increase profitability, while traditional rice farming remains economically unviable. The study found that the most significant livelihood capitals for farmers were social, natural, and human capital, with strong community interactions, active farmer groups, and access to agricultural equipment enhancing social capital. The availability of extensive land, irrigation, and labor resources facilitated the transition to horticulture. These findings suggest that horticultural diversification can offer better economic returns than traditional rice farming, with potential for replication in other regions. Future research should explore the long-term impacts and policy support needed for promoting diversified farming systems.